Mucuna guangxiensis, a new species of Mucuna subg. Macrocarpa (Leguminosae-Papilionoideae) from China - Jiang, Kaiwen; Huang, Yunfeng; Moura, Tânia M. (Phytotaxa, 2020)
Mucuna guangxiensis sp. nov. (Fabaceae), a woody liana species bearing pods up to 70 cm long, which is only known from Guangxi Province in China, is described and illustrated here. The new species is similar to Mucuna macrocarpa but differs from it by totally yellowish or greenish white corolla and more densely sericeous hairs on the abaxial surface; and also to Mucuna birdwoodiana but differs from it by the thinly papyraceous leaves, the dense indumentum on the abaxial surface of leaflets, and the longer legumes without paired robust wings at both margin. This new species should be a new member of Mucuna subg. Macrocarpa according to its long ovary, numerous seeds per legume and linear and long legumes with woody epicarp, and a detailed key of the subgenus is provided in this article.